AKTIVITAS ANTIJAMUR ASAP CAIR DARI SEBUK GERGAJI KAYU AKASIA (Acacia mangium WILLD) dan KAYU LABAN (Vitex pubescens VAHL) - H. A. Oramahi -; Farah Diba -; Wahdina - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2011)
Antifungal Activity of Liquid Smoke from Acacia mangium Willd and Vitex pubescens Vahl Wood Wastes. Aspergillus flavus is the most important fungi species because of its toxygenic characteristic on agricultural product. This research was conducted to test of wood vinegar as antifungal activity. The research was conducted in several steps i.e. pyrolisis of liquid smoke, analysis of liquid smoke content, and efficacy test of liquid smoke as antifungal. Liquid smoke was made from burning wood meal from wood wastes. Wood wastes consist of Acacia mangium Willd (akasia) and Vitex pubescens Vahl (laban). Agar media used was PDA (potatoes dextrose agar) and concentration of liquid smoke was 0, 1, 2, and 3% (v/v). The results indicated that the liquid smoke has inhibited the fungi growth. The liquid smoke with concentration of 2% had index anti fungal 80.19-100%. The growth rate of A. flavus was decrease as well as increasing the concentration of liquid smoke. The contents of organic fraction of liquid smoke, such as acid and phenol might be responsible for the difference in antifungal activities among these liquid smokes.Key words: Wood wastes, liquid smoke, Aspergillus flavus, antifungal activity